THE RELATION OF THE SPLEEN TO BLOOD DESTRUCTION AND REGENERATION AND TO HEMOLYTIC JAUNDICE : X. CONCERNING THE SUPPOSED REGULATORY INFLUENCE OF THE SPLEEN IN THE FORMATION AND DESTRUCTION OF ERYTHROCYTES. - Krumbhaar, E. B. (The Rockefeller University Press, 1914)
1. The blood of the splenic artery and vein shows either no differences, or only such slight irregular variations as may be due to the errors inherent in hematologic methods, or are common to arterial and venous blood of the general circulation. 2. The observation of Banti and Furno that free hemoglobin occurs in the blood of the splenic vein is not confirmed. 3. Extracts of the spleen have no definite hemolytic action in vitro. 4. Intraperitoneal injection of fresh saline extracts of the spleen causes in the dog a sharp increase in the number of red cells and the hemoglobin content which lasts for one or two days and may recur on a second injection. Extracts of liver, kidney, and erythrocytes similarly prepared do not give this effect. This observation supports Danilewsky's theory that the spleen may exert a stimulating effect upon the formation of red cells in the bone marrow. 5. On the other hand, the feeding of raw beef spleen to splenectomized dogs over long periods of time has no clearly defined influence in preventing the anemia which usually follows splenectomy.